Association of 5-Alpha Reductase Inhibitor Use with Prostate Specific Antigen Level at the Time of Urology Referral in a Retrospective Cohort at a Large, Integrated Health Care System. Issue 6 (23rd November 2021) - Kearns, James T.; Matulay, Justin T.; Anderson, William E.; Hetherington, Timothy C.; Grigg, Claud M.; Zhu, Jason; Gaston, Kris E.; Riggs, Stephen B.; Burgess, Earle F.; Clark, Peter E.
Abstract: Introduction: 5-Alpha reductase inhibitor (5-ARI) use leads to a 50% decline in serum prostate specific antigen (PSA) without a concomitant decrease in prostate cancer (PCa) risk. We hypothesize that failure to account for the effect of 5-ARI use on serum PSA leads to increased PCa risk at urology referral among 5-ARI users. Methods: This is a retrospective cohort study for the years 2018–2019. Atrium Health is a large, vertically integrated health system with over 900 care locations in North Carolina and South Carolina. Men ≥40 years old during 2018–2019 who had a PSA test performed were included. We determined differences in corrected serum PSA level at the time of referral to urology. 5-ARI users and nonusers were compared using the chi-square test, Student's t-test and gamma regression. Results: From 2018–2019, there were 91, 368 men who underwent PSA testing, including 2, 939 5-ARI users. At referral, 5-ARI users had similar uncorrected median PSA (5.8 vs 5.6 ng/ml, p=0.05). After correcting for the effect of 5-ARIs on PSA, 5-ARI users had a median PSA of 11.6 ng/ml at urology referral, compared to 5.6 ng/ml in nonusers. Conclusions: Men taking 5-ARIs have higher corrected serum PSA at time of referral to urology. As the unadjusted PSA at referral to urology for PCa risk was similar between 5-ARI users and nonusers, this indicates that the effect of 5-ARI use on serum PSA levels is not routinely accounted for when assessing PCa risk.